Wear Enhancement of High Yield Steels using Laser Cladding - D. C. Cuculea; C. Iatan; G. Ardelean; E. M. Stanciu; A. Pascu (Annals of "Dunarea de Jos" University of Galati, Fascicle XII, Welding Equipment and Technology, 2024)
Laser cladding is a process that uses laser beam as a heat source to melt metallic powder, generating a layer that improves or produces a new surface. The current study aims to improve the base material surface by applying a layer of high alloy nickel via the coaxial laser cladding procedure. The experimental tests were conducted utilizing S700MC steel as base material, owing to its widespread industrial application in agriculture for various components. The cladding tests were performed with a Trumpf TruPulse 556 pulsed laser and a PRECITEC coaxial cladding module. To determine mechanical behaviour, the samples were analysed using optical and electronic microscopy, EDS, microhardness, and wear resistance. The results show that NiCrBSi powder is a suitable material for repairing the S700MC steel and increase the lifespan of components.